Development of dynamic phasors for the modelling of aircraft electrical power systems - Yang, Tao (2013)
As the More-Electric Aircraft (MEA) has been identified as a major trend of future aircraft, the on-board Electrical Power System (EPS) will see significant increased numbers of Power Electronic Converters (PECs) and motor drive systems. In order to study the behaviour and performance of the EPS in MEA, extensive simulation studies need to be done during the system design process. This in return, gives the need to have computationally efficient and accurate models to reduce the design period. In this thesis, the Dynamic Phasor (DP) is used for modelling EPS in the MEA. The DP technique is a general averaging method and naturally a frequency-domain analysis tool. Compared with other averaging models, which is only efficient under balanced conditions, the DP model maintains efficiency under both balanced and unbalanced conditions. The DP technique has been widely used in modelling the constant, single frequency EPS. In this thesis, the DP technique is extended to modelling time-varying frequency EPS. The application of DP in modelling a multi-generator, multi-frequency system is for the first time, developed in this thesis. The developed theory allows a wider application of the DPs. The developed DP model covers key elements in MEA electrical power systems, including the synchronous generator, control, transmission lines, uncontrolled rectifiers, PWM converters and 18-pulse autotransformer rectifier units. The DP model library developed based on this thesis allows the flexibility to study various EPS’s by integrating elements from the library. A twin-generator aircraft EPS, which is based on the More Open Electrical Technology (MOET) large aircraft EPS architecture, is used to demonstrate the application of DP models. Comparing the DP model with the ABC model (models in three-phase coordinates) and the DQ0 model (models in a synchronous dq frame), the efficiency and the accuracy of the DP model are demonstrated under both balanced and unbalanced conditions.